Comparing seroma formation rate after harvest of the deep inferior epigastric artery perforator flap and the superficial abdominal perforator flaps in autologous breast reconstruction: A propensity‐matched analysis. Issue 1 (30th September 2022) - Nakatsuka, Kengo; Fuse, Yuma; Karakawa, Ryo; Yano, Tomoyuki; Yoshimatsu, Hidehiko
Abstract: Background: Donor site seroma formation and prolonged drainage duration are commonly seen after harvest of perforator‐based abdominal flaps. The lymphatic network including the lymphatic vessels and the lymph nodes can be traumatized during harvest of a perforator‐based abdominal flap, eventually causing seroma formation. The aim of this study was to compare postoperative seroma occurrence rates between the deep system group including the deep inferior epigastric artery perforator (DIEP) flap and the superficial system group comprised of the superficial inferior epigastric artery (SIEA) flap, the superficial circumflex iliac artery perforator (SCIP) flap, and the SIEA‐SCIP combined flap. Patients and methods: A retrospective analysis of all patients who underwent unilateral breast reconstruction using perforator‐based abdominal flaps from June 2020 to May 2021 was performed. The patients were divided into the deep system group and the superficial system group. Propensity score matching was used to compare in the two groups the mean duration of drainage in the donor site and the occurrence of postoperative aspiration. Covariates included sex, age, body mass index, history of smoking, past history of diabetes mellitus. One hundred and fifteen patients (the deep system group, n  = 100 and the superficial system group, n  = 15) met inclusion criteria for a 1:1 match performed on 14 deep system group patients using propensity scores, with 14 superficial system group patients having similar characteristics. Results: The mean duration of drainage in the donor site was shorter in the deep system group (6.6 ± 1.9 days) than in the superficial system group (9.3 ± 2.3 days, p  < .01). The occurrence rate of postoperative aspiration was lower in the deep system group (0%) than in the superficial system group (50%, p  < .01). Conclusions: Although superficial abdominal perforator flaps are considered to be less invasive than the DIEP flap, they are associated with prolonged donor site drainage and more frequent occurrence rate of postoperative aspiration.